The jungle, the Japanese and the British Commonwealth armies at war, 1941-45 fighting methods, doctrine and training for jungle warfare - Morelock, J.D. 1946- (ass series--military history and policy, 2005)
This book focuses on the British Commonwealth armies during the Second World War, which, following the disastrous Malayan and Burma campaigns, had to hurriedly re-organise their troops to fight the Japanese.